2019
DOI: 10.1111/jcmm.14714
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA MEG3 knockdown attenuates endoplasmic reticulum stress‐mediated apoptosis by targeting p53 following myocardial infarction

Abstract: Mounting evidence has indicated that long non‐coding RNA maternally expressed gene 3 (lncRNA MEG3) regulates cell apoptosis, and is involved in a variety of diseases. However, its exact role in myocardial infarction (MI) has not been fully elucidated. In the present study, we firstly observed that the expression levels of the lncRNA MEG3 in infarct hearts and hypoxic neonatal mice ventricular myocytes (NMVMs) were up‐regulated by quantitative real‐time PCR (qRT‐PCR). Then, we knocked down lncRNA MEG3 by lentiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…45 Also, MEG3 inhibits the progression of prostate cancer by facilitating H3K27 trimethylation, 46 and MEG3 knockdown attenuates endoplasmic reticulum stress-mediated apoptosis. 47 Furthermore, uric acid enhances autophagy through the MEG3/miR-7-5p/EGFR axis. 48 Interestingly, MEG3 interacts with miR-494 to repress bladder cancer progression through targeting PTEN, 49 and MEG3 binds with miR-27a to promote PHLPP2 protein translation and impairs bladder cancer invasion.…”
Section: Discussionmentioning
confidence: 99%
“…45 Also, MEG3 inhibits the progression of prostate cancer by facilitating H3K27 trimethylation, 46 and MEG3 knockdown attenuates endoplasmic reticulum stress-mediated apoptosis. 47 Furthermore, uric acid enhances autophagy through the MEG3/miR-7-5p/EGFR axis. 48 Interestingly, MEG3 interacts with miR-494 to repress bladder cancer progression through targeting PTEN, 49 and MEG3 binds with miR-27a to promote PHLPP2 protein translation and impairs bladder cancer invasion.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs can also target the apoptotic process in cardiomyocytes, which can lead to myocardial infarction. P53 is also implicated in apoptosis modulation, and the lncRNA Meg3 can target p53 and subsequently modulate NF‐κB‐ and ERS‐associated apoptosis in murine ventricular myocytes 87 . Cardiac apoptosis‐related lncRNA (CARL) is able to sponge miR‐539 in mice and thus indirectly upregulate its target PHB2, which modulates apoptosis and mitochondrial fission 88 .…”
Section: Lncrnas In Obesity‐associated Diseasesmentioning
confidence: 99%
“…Previous research have showed that MEG3 modulates transient receptor potential cation channel subfamily V member 4 (TRPV4) expression to aggravate hypoxia-induced injury in rat cardiomyocytes by sponging miR-325-3p (9). MEG3 knockdown exerts cardioprotection by reducing endoplasmic reticulum stress (ERS)mediated apoptosis through targeting p53 post-myocardial infarction (10). MEG3 accelerates apoptosis of hypoxic myocardial cells via fork head box O1 (FoxO1) signaling pathway (11).…”
Section: Introductionmentioning
confidence: 99%